Staphylococcal resistance in Turkey to seven commonly used antibiotics: in vitro studies on cultures from 300 children - Akman, Muvaffak A. (The Turkish Journal of Pediatrics, 1961)
Results of antibiotic resistance tests of 300 strains of pathogenic staphylococci isolated from children at the Hacettepe Children's Hospital in Ankara, Turkey, were as follows: 66.3 % resistant to penicillin; 39 % to chloramphenicol; 27 % to streptomycin; 12% to oxytetracycline; 11.3% to tetracycline; 6% to chlortetracycline, and 0 % to erythromycin.A correlation exists between the frequency of drug administration for the treatment of staphylococcal infections and the development of staphylococcal resistant strains.Among the strains studied a statistically significant difference was found in resistance to penicillin and oxytetracycline as between strains isolated from infections of the middle ear and of the nose or throat, resistant strains being isolated more frequently from the latter sites.